2019
DOI: 10.1542/peds.2018-3943
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Preservation Outcomes in Adolescent and Young Adult Feminizing Transgender Patients

Abstract: BACKGROUND: Fertility preservation enables patients undergoing gonadotoxic therapies to retain the potential for biological children and now has broader implications in the care of transgender individuals. Multiple medical societies recommend counseling on fertility preservation before initiating therapy for gender dysphoria; however, outcome data pre-and posttreatment are limited in feminizing transgender adolescents and young adults. METHODS: The University of Pittsburgh Institutional Research Board approved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 24 publications
2
23
0
6
Order By: Relevance
“…Several studies have shown that semen parameters including sperm concentration, total motile sperm count and post-thaw motility are lower in transgender women when compared to cisgender men (3,10,17,18,22). The etiology of these findings is unknown; however, some of the reasons could be wearing tight underwear, self-induced high scrotal positioning of the testes, psychological stress, genetic factors and gender affirming hormone therapy (21,34).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that semen parameters including sperm concentration, total motile sperm count and post-thaw motility are lower in transgender women when compared to cisgender men (3,10,17,18,22). The etiology of these findings is unknown; however, some of the reasons could be wearing tight underwear, self-induced high scrotal positioning of the testes, psychological stress, genetic factors and gender affirming hormone therapy (21,34).…”
Section: Discussionmentioning
confidence: 99%
“…Il reste encore beaucoup d'interrogations sur la réversibilité de ces traitements. Celle-ci dépend probablement des durées, doses et types d'hormones déjà prescrites, ainsi que de facteurs individuels, mais elle est vraisemblablement au minimum de 3 mois (un cycle complet de spermatogénèse) [12]. Une amélioration des paramètres spermatiques chez les femmes transgenres effectuant une fenêtre thérapeutique peut être espérée [13].…”
Section: Effet Des Traitements Sur Les Fonctions De Reproductionunclassified
“…Certaines études ont publié les données spermatiques des femmes transgenres qui ont bénéficié d'une autoconservation de spermatozoïdes (Tableau 3) [12,13,[24][25][26][27]. Les publications sont peu nombreuses et les effectifs assez limités.…”
Section: Paramètres Spermatiques Et Bilan Hormonal Avant Initiation Du Traitementunclassified
See 1 more Smart Citation
“…The majority of fertility preservation counseling, as these services have low rates of utilization by transgender youth, is easily rendered in virtual visits including discussion of processes involved to undergo fertility preservation (e.g., ovulation induction for oocyte cryopreservation or sperm banking) [ [14] , [15] , [16] ]. Additionally, gender diverse youth and their guardians should be reminded that fertility preservation does not have to occur before gender-affirming hormone therapy and studies have documented both successful pregnancy and oocyte retrieval after discontinuation of testosterone, and sperm retrieval after discontinuation of estrogen [ [17] , [18] , [19] ]. Even during the pandemic, fertility preservation is an important part of counseling before medical transition.…”
Section: Medical Considerationsmentioning
confidence: 99%